MUSEOLOGICAL CONTEXTS OF LITHUANIAN HISTORY. CONSTANTS AND CHANGES IN THEMES, PROBLEMS AND TOPOGRAPHY - Keršytė, Nastazija (Acta Museologica Lithuanica, 2015)
In nineteenth to twenty-first-century Lithuania, the exhibits of almost all museums reflect a certain aspect of Lithuanian history. These exhibits are the quintessence of museum concepts and are presupposed by sočiety and the groups within it, historical memory, scientific and ideological discourses. The most important themes of Lithuanian history exhibits include Lithuanian prehistory, past glory, statehood, resistance to foreign occupation, repressions, exile, trauma, struggle for independence and its restoration and certain personalities who were involved in these processes. Exhibits of Lithuanian prehistory have remained constant since the nineteenth century. Other tendencies of Lithuanian history exhibits in museums have been shaped by time, ideology and politics. Since the Republic of Lithuania in the Interwar period (1918–1940), popular museum themes include Vytautas the Great, the Battle of Žalgiris, medieval castles, rebellions against Russia and especially the prohibition of the Lithuanian press in the nineteenth century. Since the second half of the twentieth century, the musealisation of the memory of personalities, especially writers, is intensifying. After restoring Lithuanian independence in 1990, museums have tackled the acute themes of Soviet occupation, anti-Soviet resistance, exile, trauma and Lithuania’s pursuit of independence. Current museological representations of Lithuanian history are rising, fostered by concepts of “living history” and “the past for the present”.
Keywords: museum expositions; museological themes of Lithuanian history